SPECIES DISTRIBUTION AND ANTIBIOTIC SUSCEPTIBILITY PROFILE OF BACTERIAL URO-PATHOGENS AMONG PATIENTS DIAGNOSED WITH URINARY TRACT INFECTION (The Research of Medical Science Review, 2025)
Background: Urinary tract infections (UTIs) are among the most frequently encountered bacterial infections worldwide. The rising antibiotic resistance among uropathogens necessitates ongoing surveillance to inform empirical treatment strategies. Objective: This study aimed to assess the species distribution and antibiotic susceptibility patterns of bacterial uropathogens isolated from patients with UTIs. Methods: This cross-sectional study was conducted at the Department of Urology, Institute of Kidney Diseases, Peshawar, using consecutive non-probability sampling. A total of 131 patients aged 18–70 years, diagnosed with UTI, were included. Midstream urine samples were cultured on Blood Agar and CLED media. Organisms with ≥10⁵ CFU/mL were considered significant. Antibiotic susceptibility testing was performed using the Kirby-Bauer disk diffusion method, and results were interpreted according to CLSI guidelines. Results: The mean age of patients was 43.5 ± 12.3 years, with 62.6% being female. Escherichia coli was the most frequently isolated organism (56.5%), followed by Klebsiella pneumoniae (12.2%), Proteus mirabilis (9.9%), and Pseudomonas aeruginosa (7.6%). E. coli showed high sensitivity to Nitrofurantoin (90.5%) and Amikacin (86.5%), while resistance was highest to Ampicillin (75.7%) and Ciprofloxacin (62.2%). Stratification revealed a higher prevalence of E. coli among females (p=0.036) and a significant association of Klebsiella with diabetes (p=0.021) and Pseudomonas with chronic kidney disease (p=0.019). Conclusion: It is concluded that E. coli remains the leading uropathogen in UTIs, with growing resistance to commonly used antibiotics. Nitrofurantoin and Amikacin demonstrated high efficacy and may be recommended as empirical choices. Continuous local surveillance and antibiotic stewardship are essential to combat resistance and guide appropriate therapy.